Цифровізація економіки: виклики та можливості - Нуреддін Хусейн Хашем (ХНУРЕ, 2024)
Today's dynamically developing socio-economic landscape and rapid scientific and technological progress are driving the inevitable digitalization of all spheres of life, including both the national and global economy. This process, in addition to fundamental changes in business and market functioning, brings a set of new challenges and prospects that require careful analysis and a systematic approach
Keywords: цифровізація економіки; socio-economic landscape